Navigating identity: the experiences of Chinese women adopted into families - Neider, Eve; Wang, Xiafei; Guan, Ting (Frontiers in Sociology, 2025)
IntroductionThis qualitative study explores the experiences of 12 Chinese women, aged 18–22, adopted by White families in the United States. While China’s one-child policy led to the international adoption of thousands of Chinese girls (1979–2015), qualitative research on their perspective about their adoption and cultural identity remains limited. Adoption is often misunderstood and stigmatized, particularly regarding its lasting impact. This study uses the intersectionality theoretical framework to understand the unique experiences of being Asian and adopted.Methods12 participants took part in 60- to 90-min semi-structured interviews conducted in person or via Zoom. 17 questions explored topics such as feelings about adoption, identity, and experiences with racism. Narrative and thematic content analysis were used to interpret the data.ResultsAll participants expressed gratitude for being adopted but many felt embarrassed and uncomfortable discussing adoption, especially in childhood. Their environments shaped how they navigated identity—those in less diverse areas felt especially alienated. Many identified more with White culture than Asian culture. Most felt a stronger connection to White culture than to their Asian heritage and faced challenges being fully accepted by either White or culturally Asian peer groups. Every participant recounted instances of racism or being subjected to stereotypes.DiscussionFindings emphasize the importance of awareness and support from families, peers, and professionals. Social workers should consider adoptees’ cultural identity and emotional experiences in assessments and therapy. Educating adoptive families and partners on racial and cultural dynamics can reduce isolation and strengthen support for transracial adoptees.